2004
DOI: 10.1289/ehp.6641
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Insecticide Exposures and Birth Weight and Length among an Urban Minority Cohort

Abstract: We reported previously that insecticide exposures were widespread among minority women in New York City during pregnancy and that levels of the organophosphate chlorpyrifos in umbilical cord plasma were inversely associated with birth weight and length. Here we expand analyses to include additional insecticides (the organophosphate diazinon and the carbamate propoxur), a larger sample size (n = 314 mother–newborn pairs), and insecticide measurements in maternal personal air during pregnancy as well as in umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
352
5
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(390 citation statements)
references
References 26 publications
29
352
5
4
Order By: Relevance
“…Por outro lado, não foi observado um padrão similar em relação ao baixo peso ao nascer, o qual tem sido associado com a exposição a agrotóxicos, tanto no Brasil 23 , como em outros países 15,29,30,31 .…”
Section: Resultsunclassified
“…Por outro lado, não foi observado um padrão similar em relação ao baixo peso ao nascer, o qual tem sido associado com a exposição a agrotóxicos, tanto no Brasil 23 , como em outros países 15,29,30,31 .…”
Section: Resultsunclassified
“…Low-level exposure to chlorpyrifos has caused adverse developmental effects in human pregnancies, such as low birth weight and reduced head circumference. 7,8 Chlorpyrifos is also considered to be an endocrine disrupting compound, 9 and some recent studies have shown an association between chlorpyrifos exposure and both lung and prostate cancer. 10,11 Exposure assessment using probabilistic techniques have been shown to be an effective tool in environmental health risk assessment, in which the exposure values are presented in cumulative probability distributions rather than the traditional single-point exposure estimate.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide exposure has been associated with increased risks of childhood cancer (Daniels et al, 1997;Reynolds et al, 2002); child neurodevelopment (Rosas and Eskenazi, 2008); fetal growth outcomes (Arbuckle and Sever, 1998;Whyatt et al, 2004); adult cancers (Alavanja et al, 2004) such as non-Hodgkin's lymphoma, leukemia, and breast cancer; and neurological effects (Sanborn et al, 2007). Several nationaland regional-scale studies have been conducted, demonstrating that up to 90% of US households used pesticides in their house, garden, or yard, and more than half of the products applied were insecticides (Savage et al, 1981;Davis et al, 1992;Whitmore et al, 1994;Adgate et al, 2000;Colt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%